Reinterpretation of God: Islamic Kalam Thought in the Era of Global Multiculturalism - Jauharotina Alfadhilah; Euis Faridah; Hasan Akbar Fathullah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
God is a transcendent reality that has long been the central object of metaphysical and theological inquiry. In the Islamic intellectual tradition, particularly within the discipline of kalam, the discourse on God has produced diverse interpretations regarding His essence, attributes, and existence. In the contemporary era of global multiculturalismcharacterized by plural traditions, worldviews, and intercultural encounters the question of how kalam thought about God remains relevant and requires renewed interpretation. The purpose of this study is to reinterpret the concept of God in Islamic kalam thought and to explore its relevance for fostering tolerance, intercultural dialogue, and religious coexistence in the context of global multiculturalism. To achieve this, the research employs a qualitative method with a theoretical-hermeneutical approach, focusing on textual analysis and interpretative reflection on classical and modern kalam discourses. The findings indicate that, according to kalam thought, God is One, possesses both essence (dhat) and attributes (sifat), exists necessarily by Himself, and His existence is independent of human acknowledgment. The plurality of views concerning God within Islamic theology and among world religions should not be regarded as a weakness, but rather as an opportunity to nurture tolerance and mutual respect. In this sense, the reinterpretation of God through kalam thought contributes not only to strengthening rational faith but also to building bridges of dialogue in today’s pluralistic and multicultural society.